A construção discursiva da mulher na revista hyloea do colégio militar de Porto Alegre : uma abordagem dialógica - Oliveira, Patrícia Flasmo de (2019)
This work consists in analysing how the feminine women are discursively built during dialogic relationships in the Magazine Hyloea between the years of 1922 and 1938, a period in which it was a literary publication and official organ of the Civic and Literary Society of the Military School of Porto Alegre. The aim of the present research has been to investigate the images of women through texts written by students or collaborators of the Magazine, verifying the way these images are built separately by men and by women to see how each group interprets the notion of feminine under the same sociocultural context.